Enterokinase Intestinal Enterokinase Deficiency in Pediatrics - Abdelsamie Fadl, Ahmed; Ahmed Alabdullatif, Abdulhalim; Moluk Nabeel S, Aldebani; Mohammed Abdullah S, Alqahtani; Ebrahim Khalil Maki, Dania; Maryam Eyadah, Alharbi; Yahya Sufi, Waleed; Saleh A Alharbi, Abdullmajeed; Mohammed J Alzahrani, Nada; Ali A Alshamrani, Mohammed; Abdullah Bugshan, Ahmed; Ibrahim A Altowairqi, Abdulrahman; et al. (International Journal of Life Science and Pharma Research, 2022)
Abstract: Congenital enteropeptidase deficiency (CEP), also known as enterokinase deficiency. CEP is an uncommon autosomal recessive genetic disorder mostly characterized by severe chronic diarrhoea after delivery, hypoproteinemia, and failure to grow. Enteropeptidase activity is anticipated to play a significant role in protein digestion. For growth and appropriate development in newborns with a congenital lack of the enzyme, pancreatic enzyme replacement treatment or an amino acid combination must be given. Only 13 cases of enterokinase insufficiency have been recorded since it was originally characterized in 1969. Couples should be informed that prenatal screening is an option and that EKD has a favourable prognosis. However, if an EKD patient is born, parents should be aware of the feeding issue and offer the proper pancreatic exocrine secretion medication. One research found that all patients had been diagnosed as newborns 25 years ago. Even when the pancreatic-enzyme replacement was stopped, they appeared to lead regular lives as adults, free of gastrointestinal issues and with normal body weight. This can be explained by the fact that trypsin, once liberated from its precursor, encourages additional trypsinogen activation in a positive-feedback manner. Better pharmaceutical preparations such as enteric-coated minimicrospheres and delayed-release capsules are used for better results as it maintains the enzyme and prevents its breakdown by stomach acidity. This review aims to summarise current knowledge of pathophysiology, causes, and treatment of Intestinal Enterokinase Deficiency in Pediatrics